Threats and Vulnerabilities of the Banking System to Money Laundering in the Arab Maghreb: Lessons from a Regional Sectoral Assessment - Belalmi fahd; Attari abdennasser (المجلة الدولية للأداء الاقتصادي)
This research paper conducts a sectoral assessment of the threats and vulnerabilities faced by the banking systems of the Arab Maghreb—specifically Algeria, Tunisia, Morocco, Libya, and Mauritania—regarding money laundering and terrorist financing. The main objective is to identify and compare structural and operational weaknesses across the region’s banking sectors, with a focus on internal controls, regulatory compliance, and the effectiveness of supervisory frameworks. The study hypothesizes that institutional fragmentation, inconsistent supervision, and insufficient risk management contribute significantly to these vulnerabilities. Methodologically, the research employs a qualitative comparative approach, drawing on national sectoral risk assessments, semi-structured interviews with stakeholders, and a review of regulatory and institutional frameworks, structured around the Financial Action Task Force (FATF) methodology. Key findings reveal a moderately high level of vulnerability within the Maghreb banking sector, driven by deficiencies in beneficial ownership identification, inconsistent regulatory enforcement, limited technological and analytical capacity, and insufficient staff training. High-risk areas include large-scale cash transactions, politically exposed persons, real estate, and the use of digital and crypto-asset channels. The study also highlights the impact of the informal economy, transnational organized crime, and weak trade oversight as external risk factors. Notably, the risk-based approach (RBA) has yet to be fully institutionalized, and supervision remains largely compliance-based rather than risk-sensitive.The implications of these findings underscore the urgency of strengthening internal controls, adopting advanced technological solutions, enhancing staff training, and modernizing regulatory frameworks in line with international standards. Recommendations emphasize the need for improved inter-authority coordination, adoption of risk-based supervision, and greater regional and international cooperation to mitigate evolving money laundering and terrorist financing threats. The research concludes that aligning Maghreb banking systems with global best practices is essential for enhancing financial integrity and resilience.